REVITALIZING HIGH SCHOOL EDUCATION MANAGEMENT IN THE DIGITAL ERA: CHALLENGES AND OPPORTUNITIES FOR EDUCATIONAL TRANSFORMATION - Hidayat, Moh Hyang (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research examines efforts to revitalize educational management at Nurul Hidayah High School. The main focus of this study is to understand the challenges and opportunities faced by the school in dealing with the changing dynamics of education in the digital era. Using a case study approach and qualitative methodology, the research involves in-depth interviews, observations, and document analysis. The findings indicate that Nurul Hidayah High School faces several challenges, such as difficulties integrating technology into the learning process, a lack of digital skills among teachers, and the need to expand the curriculum to respond to students' needs in the digital era. The school has implemented various strategies to revitalize educational management to address these challenges. These efforts involve intensive training for teaching staff, strategic partnerships with the technology industry, and adjustments to teaching strategies in line with technological developments. Despite facing challenges, Nurul Hidayah High School has also been able to identify opportunities for educational transformation. The utilization of technology as an innovative learning tool improved accessibility to education, and the development of a management model responsive to the needs of digital students are part of the steps taken by the school. This research contributes to a better understanding of the complexity of revitalizing educational management in the digital era, particularly in the context of high schools in the Banyuputih region, Bondowoso. The implications of these findings can serve as a guide for other educational institutions facing similar challenges in pursuing opportunities for educational transformation in the digital era